Implementasi Model Project Based Learning Untuk Meningkatkan Kemampuan Berpikir Kritis dan Karakter Peserta Didik Pada Materi Tata Surya di Kelas VII SMP Negeri 2 Amarasi Satap - Eufrasia Kristina Samin; Alfons Bunga Naen; Egidius Dewa (MAGNETON: Jurnal Inovasi Pembelajaran Fisika UNWIRA, 2023)
This study aims to determine the improvement of critical thinking skills and character of students in class VII junior high school after using models of project-based learning on solar system material. This study used a one-group pretest-posttest design, the instruments used were concept understanding test questions and character observation sheets. The result showed that the average understanding of critical thinking in the pre-test was 52% with a moderate category and the post-test was 88% with a high category. The N-Gain value of students' critical thinking is 0,67 with a moderate variety. In contrast, the average character of students is 54% with a moderate category. The result showed that the use of Project Based Learning Models of the solar systems contributed to the improvement of critical thinking and character interest of good students in class VII Junior High School.